Multiple fouling dynamics, interactions and synergistic effects in brackish surface water distribution systems. (January 2022) - Muhammad, Tahir; Li, Lei; Xiao, Yang; Zhou, Yunpeng; Liu, Zeyuan; He, Xin; Bazai, Nazir Ahmed; Li, Yunkai
Abstract: Dissolved salts, colloidal particles, and active microorganisms in brackish surface water distribution systems (BSWD) cause multiple fouling, poses potential threat to the environmental pollution, and raising technical and economic issues as well. So far, the co-occurrence and interactions of multiple fouling remains largely unknown. Multiple fouling behaviors were assessed in agriculture BSWD under different nitrogen (N) fertilizers. X-ray diffraction, Rietveld refinement analysis, 16S rRNA, and microbial network analysis were conducted to determine the fouling characteristics. Statistical analysis was applied to reveal the relative contributions and interaction of multiple fouling. Our results demonstrated, multiple fouling of precipitates, particulates and biofoulings were co-occurred. Fouling growth was largely attributed to the strong interactions of different fouling. The binary interactions of precipitates - particulates contributed 51.1%, and ternary interactions of precipitates - particulates - biofouling contributed 25.4% to explain the decline of system performance, while the contribution of each single type fouling was minimal. Thereby indicating the significant role of calcium silica, biomineralization and bio-silicates in fouling. The lower acid N fertilizer broken the interaction of multiple fouling by increasing the precipitate crystal parameters and repulsive forces amongst particulates, as well as destroyed microbial interactions in biofouling. Overall, this study open frontier for multiple fouling in-depth profiling and antifouling guidance for effective utilization of BSWD. Graphical abstract: Image 1 Highlights: Dynamics of multiple fouling were analyzed in brackish water distribution systems. Influence pathway and interaction effects of multiple fouling were characterized. Binary 51.1% and ternary (25.4%) interactions were predominant in multiple fouling. Acid_N reduced the fouling by changing lattice parameters and microbial interaction.